If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t = 3t + 1 Reorder the terms: 2t = 1 + 3t Solving 2t = 1 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 2t + -3t = 1 + 3t + -3t Combine like terms: 2t + -3t = -1t -1t = 1 + 3t + -3t Combine like terms: 3t + -3t = 0 -1t = 1 + 0 -1t = 1 Divide each side by '-1'. t = -1 Simplifying t = -1
| 62=3c+8 | | d-257x=8328 | | 3r^2-3r-15= | | x/6-18=0 | | (x^2)-4x-32= | | 3a+7=4a+9 | | 11x-(7x-2)=10 | | (5a+6)=2(3a+8) | | 5x^2-25x=30 | | x^2+25x-224=0 | | 12cos(x)-6=0 | | -39=-6+3(x-3) | | 14+3n=7b-7.4 | | (-3/4x+24)+2=-1/x+6 | | 450-3x=300 | | -2x+6=-8 | | 2t-3(6-t)=7-(-11) | | k.5-6=2 | | x2+x=-15/4 | | m+5=16 | | x-15/21=6/7 | | 69+15= | | 1-2x^2+x=0 | | p=(2*24)+(2*51) | | 3x+2=2(x-5)+4 | | 71/3/3/2 | | 5y+13=3 | | z-(-1.4)=7.8 | | 40-9k=-10 | | 4.7-2.1x=-7.9 | | -25x+5y=40 | | -6X-4=-46 |